2016
DOI: 10.1093/humrep/dew301
|View full text |Cite
|
Sign up to set email alerts
|

Parental contributions to early embryo development: influences of urinary phthalate and phthalate alternatives among couples undergoing IVF treatment

Abstract: STUDY QUESTION: Are preconception urinary concentrations of phthalates and phthalate alternatives associated with diminished early stage embryo quality in couples undergoing IVF?SUMMARY ANSWER: Male, but not female, urinary concentrations of select metabolites of phthalates and phthalate alternatives are associated with diminished blastocyst quality.WHAT IS KNOWN ALREADY: Although phthalates are endocrine disrupting compounds associated with adverse reproductive health, they are in widespread use across the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 39 publications
4
27
1
Order By: Relevance
“…The effects of other male reproductive toxicants on embryonic development have been explored. Phthalate metabolites, measured in urine of male clinical subjects, show modest associations with blastocyst quality in assessment of in vitro fertilization (Wu et al, 2017). The results taken together indicate that low-dose EMGE exposures could pose a preconception threat to offspring of exposed fathers.…”
Section: Discussionmentioning
confidence: 87%
“…The effects of other male reproductive toxicants on embryonic development have been explored. Phthalate metabolites, measured in urine of male clinical subjects, show modest associations with blastocyst quality in assessment of in vitro fertilization (Wu et al, 2017). The results taken together indicate that low-dose EMGE exposures could pose a preconception threat to offspring of exposed fathers.…”
Section: Discussionmentioning
confidence: 87%
“…A recent study on American couples undergoing IVF treatment showed an association between paternal exposure to phthalates and poor quality of blastocysts . Here too, a potentially underlying epigenetic mechanism was not further verified.…”
Section: Do Environmental Conditions Of a Future Father Affect Offsprmentioning
confidence: 86%
“…Given that phthalates may exert effects on both gametes and embryos, studies assessing exposure before conception as well as during pregnancy are necessary. Moreover, new and emerging research suggests that the preconception period may be highly sensitive to environmental perturbations and paternal preconception exposure may be an important and largely unexplored determinant of offspring health (Braun et al 2017; Wu et al 2016). Thus, we aimed to investigate whether paternal and maternal preconception and maternal prenatal urinary phthalate metabolite concentrations were associated with infant birth weight using a prospective cohort of couples undergoing treatment in a large fertility center.…”
Section: Introductionmentioning
confidence: 99%